Factors that Influence the Application of the Concept of New Green Areas in Residential Areas Using Structural Equation Modeling-Part Least Square (SEM-PLS) - Amalia, Nur; Husin, Albert Eddy; Prastowo, Ferdiansyah Ibnu (ASTONJADRO, 2023)
Climate change and global warming or environmental damage and degradation have led to various natural disasters, social disasters and serious economic disasters. Global warming has increasingly affected not only our daily lives but also our business activities. Housing and settlements are one of the basic human needs that must be met to be able to live decently. However, human life and its business activities have not paid enough attention to environmental issues. Excessive exploitation of non-renewable energy beyond normal limits is also damaging to the environment.  The application of the new green  area concept is a consequence of the  increase in the cost of green areas  incurred by stakeholders so  that residential areas  become environmentally friendly, the concept of  new green areas, Value Engineering (VE), Life Cycle Cost Analysis (LCCA) are  the main factors  that influence the improvement of cost performance of implementing the concept    new green  areas in residential areas in Indonesia, using structural equation model- partial least square (SEM-PLS) analysis. This research has an update related to the concept of applying new green areas  to residential areas in Indonesia.  The results of this study obtained "10 factors that affect the cost performance of new green areas  in residential areas", namely Project Management, Infrastructure and Facilities Burdens, Infrastructure and Facilities Service Functions, Microclimate and Ecosystem Preservation, Environmentally Friendly Materials, Development, Cost Breakdown Structure, LCC Analysis, Evaluation, Value Engineering.